Crisis Communication in the Time Of COVID-19: The Significance of Grassroot Initiative in Democratic Countries (Case of Brazil, Indonesia, and the United States) - Marshell Adi Putra; Ignasius Loyola Adhi Bhaskara; Anggia Valerisha (Journal of Indonesian Social Sciences and Humanities, 2021)
All countries are adapting to the dynamics and changes posed by the global pandemic of COVID-19. The government is expected to act immediately and effectively in response to the crisis, particularly through public communication to their respective citizens. In this regard, crisis communication is vital to minimize the loss and damage caused by the pandemic in various aspects of life. Being able to communicate in the right and effective way during a crisis can determine the overall outcome of the situation. This paper explores on how crisis communication has conducted in the time of COVID-19 by comparing three respective democratic governments: Brazil, Indonesia, and the United States. Through qualitative method, this paper argues that in a democratic society where openness and freedom of speech is guaranteed, the process to disseminate information through crisis communication could be a daunting task. The study indicated at least four main factors that could hinder the effectiveness of crisis communication: 1) a large population and politically divide in the society; 2) the lack of coordination between levels of governments; 3) the governments’ lack of capability to communicate with the public; and 4) an incompetent crisis communication strategy. The study also found some of the grassroot initiative which is seen significance to fill the information gaps left by the government.